2005
DOI: 10.1111/j.1460-9568.2005.04159.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective dopamine D3 receptor antagonism by SB‐277011A attenuates cocaine reinforcement as assessed by progressive‐ratio and variable‐cost–variable‐payoff fixed‐ratio cocaine self‐administration in rats

Abstract: In rats, acute administration of SB-277011A, a highly selective dopamine (DA) D(3) receptor antagonist, blocks cocaine-enhanced brain stimulation reward, cocaine-seeking behaviour and reinstatement of cocaine-seeking behaviour. Here, we investigated whether SB-277011A attenuates cocaine reinforcement as assessed by cocaine self-administration under variable-cost-variable-payoff fixed-ratio (FR) and progressive-ratio (PR) reinforcement schedules. Acute i.p. administration of SB-277011A (3-24 mg/kg) did not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
135
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 79 publications
16
135
1
Order By: Relevance
“…Thus, the present finding that blockade of D 3 receptors by NGB 2904 significantly inhibits cocaine selfadministration under PR reinforcement conditions suggests that NGB 2904 antagonizes cocaine's rewarding efficacy and therefore its incentive motivational properties. This finding is consistent with previous studies demonstrating that the selective D 3 receptor antagonist SB-277011A also inhibits cocaine-seeking behavior under PR and second-order reinforcement conditions, but not under FR reinforcement conditions (Di Ciano et al, 2003;Gilbert et al, 2003;Xi et al, 2005). …”
Section: Ngb 2904's Inhibition Of Cocaine Self-administration Under Psupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, the present finding that blockade of D 3 receptors by NGB 2904 significantly inhibits cocaine selfadministration under PR reinforcement conditions suggests that NGB 2904 antagonizes cocaine's rewarding efficacy and therefore its incentive motivational properties. This finding is consistent with previous studies demonstrating that the selective D 3 receptor antagonist SB-277011A also inhibits cocaine-seeking behavior under PR and second-order reinforcement conditions, but not under FR reinforcement conditions (Di Ciano et al, 2003;Gilbert et al, 2003;Xi et al, 2005). …”
Section: Ngb 2904's Inhibition Of Cocaine Self-administration Under Psupporting
confidence: 92%
“…In the present study, we found that NGB 2904 had no significant effect on cocaine self-administration under FR2 reinforcement conditions, but significantly lowered the break-point for cocaine self-administration under PR reinforcement conditions. This is congruent with previous findings that the selective D 3 receptor antagonist SB-277011A inhibits cocaine self-administration under a PR reinforcement schedule, but not under a low-cost highpayoff FR reinforcement schedule (Di Ciano et al, 2003;Gilbert et al, 2003;Gál and Gyertyán, 2003;Xi et al, 2005). There are three possible explanations for the ineffectiveness of NGB 2904 on FR cocaine self-administration.…”
Section: Ngb 2904's Inhibition Of Cocaine Self-administration Under Psupporting
confidence: 91%
See 2 more Smart Citations
“…D3R KO mice also exhibit an increase in cocaine cue-conditioned hyperactivity and cocaine cueconditioned mice had increased levels of D3R mRNA in the nucleus accumbens compared to saline controls (Le Foll et al, 2002). It should be noted, however, that the effects of agonists and antagonists having preferential affinities for D3R over D2R are not entirely consistent with the effects observed with the more specific genetic manipulations of these receptor subtypes (eg Corbin et al, 1998;Le Foll et al, 2002;Xi et al, 2005). The development of more subtypeselective D 2 -family ligands or perhaps a double KO mouse in which both D2R and D3R are deleted would help to clarify the respective roles of these DA D 2 -family receptor subtypes in modulating the effects of cocaine and other psychostimulants.…”
Section: Discussionmentioning
confidence: 98%